Integrating Gamification into Deep Learning in Elementary Education - Rahmawati, Emma; Inayah, Zaidatul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study examines the integration of gamification into the implementation of deep learning in elementary education. Deep learning is not a new curriculum, but rather a pedagogical approach that emphasizes meaningful, mindful, and joyful learning. The primary focus of this research is to analyze how gamified elements align with the principles of deep learning and how their application can enhance students’ conceptual understanding, reflective engagement, and learning motivation. This study employs a qualitative method using content analysis based on the Miles and Huberman model, with data collected from various literature sources, including scholarly journals, reference books, policy documents, and best practices in education. The findings indicate that gamification can support deep learning, especially when designed to foster connections between learning content and real-life experiences (meaningful), involve students in reflection and responsibility for their own learning (mindful), and create an interactive and enjoyable classroom environment (joyful). The study also reveals that this approach aligns with the development of foundational literacies, 21st-century competencies, and adaptive character traits that are relevant to the needs of learners in the digital age. It is concluded that gamification holds significant potential as an effective pedagogical strategy to support the transformation of elementary education through a deep learning approach.